Synthesis, biological evaluation and molecular docking study of some novel indole and pyridine based 1,3,4-oxadiazole derivatives as potential antitubercular agents - Desai, N. C.; Somani, Hardik; Trivedi, Amit; Bhatt, Kandarp; Nawale, Laxman; Khedkar, Vijay M.; Jha, Prakash C.; Sarkar, Dhiman (Bioorganic & Medicinal Chemistry Letters, 2016)
A series of indole and pyridine based 1,3,4-oxadiazole derivatives 5a-t were synthesized and evaluated for their in vitro antitubercular activity against Mycobacterium tuberculosis H37Ra (MTB) and Mycobacterium bovis BCG both in active and dormant state. Compounds 5b, 5e, 5g and 5q exhibited very good antitubercular activity. All the newly synthesized compounds 5a-t were further evaluated for antiproliferative activity against HeLa, A549 and PANC-1 cell lines using modified MTT assay and found to be noncytotoxic. On the basis of cytotoxicity and MIC values against Mycobacterium bovis BCG, selectivity index (SI) of most active compounds 5b, 5e, 5g and 5q was calculated (SI = GI(50)/MIC) in active and dormant state. Compounds 5b, 5e and 5g demonstrated SI values >= 10 against all three cell lines and were found to safe for advance screening. Compounds 5a-t were further screened for their antibacterial activity against four bacteria strains to assess their selectivity towards MTB. In addition, the molecular docking studies revealed the binding modes of these compounds in active site of enoyl reductase (InhA), which in turn helped to establish a structural basis of inhibition of mycobacteria. The potency, low cytotoxicity and selectivity of these compounds make them valid lead compounds for further optimization. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: 1; 3; 4-Oxadiazole; Antitubercular activity; Cytotoxicity; Indole; Molecular docking; Pyridine

Synthesis, biological valuation, and QSAR studies of novel pyrazole bearing pyridyl oxadiazole analogues as potential antimicrobial agents - Desai, N. C.; Kotadiya, G. M.; Trivedi, A. R.; Khedkar, Vijay M.; Jha, Prakash C. (Medicinal Chemistry Research, 2016)
A new series of 1-(2-(3-(4-nitrophenyl)-1-phenyl-1H-pyrazol-4-yl)-5-(pyridin-4-yl)-1,3,4 -oxadiazol-3(2H)-yl)-3-(aryl)prop-2-en-1-ones (5a-l) were synthesized by a simple and efficient synthetic protocol. The newly synthesized compounds were characterized by IR, H-1 NMR, C-13 NMR and Mass spectroscopy. The resulting structural diversity was screened for its antimicrobial activity the following bacterial and fungal strains: two Gram-positive bacteria [Staphylococcus aureus (MTCC-96), Streptococcus pyogenes (MTCC-442)], two Gram-negative bacteria [Escherichia coli (MTCC-443), Pseudomonas aeruginosa (MTCC-1688)] and three fungal species (C. albicans, A. niger and A. clavatus). Following this, in vitro cytotoxicity activity against HeLa cell lines was measured by MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazoliumbromide] assay. The observations derived from the diverse assays were utilized for building classification models based on a binary QSAR approach termed recursive partitioning (RP) analysis to probe the physic-chemical properties influencing the SAR for molecules. The decision tree derived from RP analysis could highlight structural characteristics that discriminate the actives from inactives which can serve as guide to design molecules with improved potency. In silico ADME predictions were performed to gauge their pharmacokinetic, safety and drug likeness profile.
Keywords: 1; 3; 4-Oxadiazole; Antimicrobial activity; Cytotoxicity; Pyrazole; Pyridine; QSAR

Synthesis, biological evaluation, and molecular docking study of pyridine clubbed 1,3,4-oxadiazoles as potential antituberculars - Desai, N. C. (Synthetic Communications, 2018)
A series of pyridine clubbed 1,3,4-oxadiazole derivatives were efficiently synthesized, characterized by standard spectral techniques and evaluated for their in vitro antitubercular activity against Mycobacterium tuberculosis (MTB) H37Ra and Mycobacterium bovis BCG in active and dormant state using an established methods. Compounds 5a, 5m, and 5t were identified as the most active compounds against MTB. Molecular docking was performed against MTB enoyl-ACP (CoA) reductase (FabI/ENR/InhA) enzyme to predict the binding modes and affinity. The theoretical predictions from molecular docking could establish a link between the observed biological activity and the binding affinity shedding light into specific bonded and non-bonded interactions influencing the activity. The active compounds were studied for cytotoxicity against three cell lines and were found to be non-cytotoxic. Specificity of these compounds was checked by screening them for their antibacterial activity against four bacterial strains.
Keywords: antibacterial activity; antituberculosis activity; cytotoxicity activity